SOLO Taxonomy in a Visible Learning School: A Quasi-Experimental Design to Study the Effect of SOLO Taxonomy on Student Metacognitive Ability SOLO Taxonomy as a Framework of Designing Comprehension Strategies - Bader, Soha (2020)
Perspectives on the components of effective literacy learning have moved far from reading alone; however, effective literacy instructions address students’ growth through linguistic, cognitive, and text-specific processes (Conner et al., 2014). This study highlights the issue of how metacognitive thinking skills has become a strong foundation in literacy learning transformation where the goal is to prepare students to be able to function effectively in the real world as effective thinkers, problem-solvers and decision makers. However, there are several limitations to the implementation of metacognitive thinking skills in education that can hamper the effort of transforming the education. Therefore, this study seeks to identify a better approach in teaching thinking skills specifically in reading by exploring the feasibility of SOLO taxonomy as a questioning method which can facilitate students’ development of metacognitive thinking skills in ESL reading. In an American school in Sharjah, the central influence of this study is that it is the first to explicitly introduce a pioneering way consolidating the application of metacognitive thinking skills in the U.A.E schools. This study recommended the expansion of this approach to every school in the U.A.E where teachers and learners are obliged to focus on SOLO literacy instructions and recognize that learning has to occur at the surface, deep, and transfer levels (Fisher, Frey, & Hattie, 2016). This indicates the importance this study that seeks to identify a better approach in teaching thinking skills specifically in reading by exploring the feasibility of SOLO taxonomy as a questioning method which can facilitate students’ development of metacognitive thinking skills in ESL reading.